Effects of polyurethane membrane on septic colon anastomosis and intra-abdominal adhesions - Yılmaz, Gökhan; Özdenkaya, Yaşar; Karatepe, Oğuzhan; Tanrıkulu, Yusuf; Kamalı, Gülçin; Yalçın, Orhan (Turkish Association of Trauma and Emergency Surgery, 2021)
BACKGROUND: Anastomotic leakages and adhesions after gastrointestinal tract surgery are still a significant cause of morbidity and mortality. The rate of anastomotic leakage is 3%-8%, whereas the mortality from leakage is over 30%. Intra-abdominal sepsis is a well-known cause of anastomotic leakage. In addition, intra-abdominal adhesion is a major cause of hospital admissions and reoperations and is associated with morbidity and mortality. In this study, we aimed to investigate the effects of a polyurethane membrane on anastomotic healing and intra-abdominal adhesions. METHODS: This study used 32 Wistar albino rats divided into four groups. Standard resection of left colon 2 cm above the peritoneal reflection and colonic anastomosis were performed after causing abdominal sepsis through caecal ligation and perforation. The control groups (1 and 3) received no further treatment. The experimental groups (2 and 4) received the polyurethane membrane around the colonic anastomosis. Burst pressure, hydroxyproline, interleukin-6 (IL-6), nitric oxide (NO), tissue plasminogen activator (tPA), and tumor necrosis factor-alpha (TNF-?) levels were measured, and histopathological characteristics of the anastomosis were analyzed after re-laparotomy. Moreover, adhesion scores were measured. RESULTS: No statistically significant differences were found in the mean burst pressure levels between sacrificed animals on days three and five (p=0.259, p=0.177). When all the groups were compared, no significant difference was observed in the hydroxyproline, NO, and IL-6 levels (p=0.916, p=0.429, p=0.793, p=0.332, p=0.400, p=0.317). However, in groups 2 and 4, the tPA levels were significantly increased by Opsite therapy (p=0.001, p=0.003), and a statistically significant difference was observed in the adhesion scores (p<0.035). Groups 2 and 4 had significantly lower adhesion scores than groups 1 and 3. CONCLUSION: We found that Opsite therapy had no positive or negative effects on histopathological and biochemical healing in the experimental septic colon anastomosis model. However, the perianastomotic application of polyurethane membrane effectively decreased the intra-abdominal adhesions.

AMAÇ: Gastrointestinal sistem cerrahisinden sonra görülen anastomoz kaçağı ve adezyonlar hala önemli bir morbidite ve mortalite nedenidir.Anastomoz kaçağı oranı %3–8 iken, kaçağa bağlı mortalite oranı %30’un üzerindedir. Karıniçi sepsis anastomoz kaçağının iyi bilinen bir nedenidir. Ayrıca, karıniçi adezyon hastane başvurularının ve morbidite ve mortalite ile ilişkili reoperasyonların önemli bir nedenidir. Bu çalışmada, bir poliüretan membranın anastomoz iyileşmesi ve karıniçi yapışıklıklar üzerine etkileri araştırıldı.GEREÇ VE YÖNTEM: Bu çalışma için dört gruba ayrılmış 32 Wistar Albino sıçan kullanıldı. Çekal ligasyon ve perforasyon oluşturulduktan sonraperitoneal refleksiyonun 2 cm yukarısından standart sol kolon rezeksiyonu ve anastomozu yapıldı. Kontrol gruplarına (1, 3) herhangi bir tedavi verilmedi. Deney grubunda (2, 4) ise kolon anastomozunun etrafına poliüretan membran sarıldı. Patlama basıncı, hidroksiprolin, IL-6 (interlökin 6),NO (nitrik oksit), TPA (doku plazminojen aktivatörü), TNF-? (Tümör nekroz faktörü alfa) seviyeleri ölçüldü ve relaparotomi sonrası anastomozun histopatolojik özellikleri analiz edildi. Ayrıca adezyon skorları ölçüldü. BULGULAR: Üçüncü ve beşinci günler arasında sakrifiye edilen hayvanlar arasındaki ortalama patlama basıncı değerlerinde istatistiksel olarak anlamlı bir fark yoktu (p=0.259, p=0.177). Tüm gruplar karşılaştırıldığında, hidroksiprolin, NO, IL-6 seviyeleri arasında anlamlı bir fark gözlenmedi(p=0.916, p=0.429, p=0.793, p=0.332, p=0.400, p=0.317). Bununla birlikte, grup 2 ve grup 4’te, TPA seviyeleri poliüretan membran tedavisi ile anlamlı olarak yüksekti (p=0.001, p=0.003) ve adezyon skorlarına göre istatistiksel olarak anlamlı bir fark vardı (p<0.035). Grup 2 ve grup 4, grup1 ve grup 3’ten daha düşük adezyon skorlarına sahipti. TARTIŞMA: Biz deneysel septik kolon anastomoz modelinde poliüretan membranın histopatolojik ve biyokimyasal iyileşme üzerinde pozitif veya negatif bir etkisi olmadığını bulduk. Ancak, poliüretan membranın anastomoz çevresine uygulanması intraabdominal adezyonları etkili bir şekilde azaltmaktadır.
Poliüretan membranın karıniçi adezyonlar ve septik kolon anastomuzu üzerine etkileri
Keywords: Adhesion; Colonic Anastomosis; Intra-Abdominal Sepsis; Polyurethane Membrane; Adezyon; İntraabdominal Sepsis; Kolon Anastomozu; Poliüretan Membran